(untitled) (Salud, Arte y Cuidado, 2024)
Febrile neutropenia is the decrease in the absolute neutrophil count below 1.000, associated with fever, secondary to chemotherapy compliance. The aim of this study was to determine the clinical and epidemiological characteristics of pediatric patients with febrile neutropenia during chemotherapy, attended at the Deconcentrated Service of the University Pediatric Hospital Dr. Agustín Zubillaga. The study was descriptive and cross-sectional. The population consisted of pediatric oncology patients. The sample consisted of 67 hospitalized patients who received chemotherapy and presented febrile neutropenia in the study period from January 2018 to January 2023, who met the inclusion criteria. The data collection technique was direct observation of the histories of the patients who constituted the sample and the instrument was a structured form developed for this research. The results were the following; of the epidemiological characteristics, children from 2 to 5 years old predominate, the largest group corresponds to the male sex and they come from the state of Lara, a high percentage of the population was classified in Graffar IV. The clinical characteristics predominate in this order; respiratory symptomatology, skin and soft tissues, gastrointestinal alterations and urinary, in a high percentage of the population, febrile neutropenia was 10-12 days after the completion of chemotherapy, with benefits after the use of antibiotic therapy and cure of symptoms. In paraclinical studies, the findings indicate the absolute value of neutrophils is relevant criteria of severity, likewise, the early performance of cultures and laboratory studies in the presence of fever in post chemotherapy patients are of great importance, since it allows the early establishment of therapy and therefore lower incidence of morbidity and mortality.